2017
DOI: 10.1177/0143034317745946
|View full text |Cite
|
Sign up to set email alerts
|

Classes of trajectory in mobile phone dependency and the effects of negative parenting on them during early adolescence

Abstract: The aim of this study was to identify the classes of trajectory in mobile phone dependency using growth mixture modeling among Korean early adolescents from elementary school to the middle school transition. The effects of negative parenting on determining the classes were also examined. The participants were 2,378 early adolescents in the Korean Children and Youth Panel Survey. Three classes of trajectory in mobile phone dependency were found. Adolescents who were highly dependent on mobile phones were very f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
(33 reference statements)
2
2
0
Order By: Relevance
“…This study also found that perceived negative parenting predicts adolescent smartphone dependency. This finding is consistent with those of previous studies that indicate that neglective or harsh parenting has negative effects on adolescent smartphone dependency [6,56,57]. Adolescents who experience negative parenting may develop smartphone dependency; adverse experiences lead to psychological distress, which can in turn increase excessive smartphone use.…”
Section: Discussionsupporting
confidence: 92%
“…This study also found that perceived negative parenting predicts adolescent smartphone dependency. This finding is consistent with those of previous studies that indicate that neglective or harsh parenting has negative effects on adolescent smartphone dependency [6,56,57]. Adolescents who experience negative parenting may develop smartphone dependency; adverse experiences lead to psychological distress, which can in turn increase excessive smartphone use.…”
Section: Discussionsupporting
confidence: 92%
“…Coercive parenting attitudes positively affected female adolescents' smartphone addiction. This result was consistent with previous research findings (Seo & Choi, 2018; Yoo & Kim, 2015). Moreover, negative parenting attitudes increasing children's depression and their smartphone addiction (Yoo & Kim, 2015).…”
Section: Depressionsupporting
confidence: 94%
“…Previous studies have shown that depression worsens smartphone addiction in adolescents (Demirci et al, 2015). On the other hand, social interaction can act as protective factor against smartphone addiction, while parenting attitude can affect smartphone addiction (Seo & Choi, 2018; Yoo & Kim, 2015; You & Kwon, 2011). Additionally, in their school life, teacher influences affect smartphone addiction among adolescents (Kwak et al, 2018); however, very few studies have addressed the various aspects of teacher–student relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, depressive symptoms and PMU are significant causes of difficulty in adolescents' daily lives including their school lives (Webb et al., 2007), and many younger teenagers have started using mobile phones (Seo & Choi, 2018). Therefore, the findings of the present study can be a source for education and public policies to decrease such negative impacts of PMU from a global perspective.…”
Section: Discussionmentioning
confidence: 99%